Ru-catalyzed asymmetric transfer hydrogenation of alpha-acyl butyrolactone via dynamic kinetic resolution: asymmetric synthesis of bis-THF alcohol intermediate of darunavir - More, V. Ganesh; Malekar, V. Pushpa; Kalshetti, Rupali G.; Shinde, Mahesh H.; Ramana, V. Chepuri (Tetrahedron Letters, 2021)
The Ru-catalyzed enantio- and diastereoselective dynamic kinetic resolution of alpha-(benzyloxy/benzoyloxy)acyl-gamma-butyrolactones has been examined via transfer hydrogenation. Employing the in situ prepared (R,R)-Ru-FsDPEN catalyst, the transfer hydrogenation of using formic acid/triethylamine at rt gave the corresponding (S)-3-((S)-2-(benzyloxy/benzoyloxy)-1-hydroxyethyl)dihydrofuran-2(3H)-on e with good to excellent diastereo- and enantioselectivity. One of the resulting hydrogenation product prepared on gram scales was utilized for the synthesis of (3R,3aS,6aR)-hexahydrofuro[2,3-b]furan-3-ol (1), a key synthetic intermediate of various HIV protease inhibitors such as darunavir with excellent enantio-(95% ee) and diastereoselectivities (dr 95:5). (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Bis-THF-OH intermediate; Darunavir; Dynamic kinetic resolution; Ru-catalysis; transfer hydrogenation

Synthesis of anisotropic rod-like gold nanostructures in organic media (vol 133, 106, 2021) - Prasad, V. Bhagavatula L.; Sivasankaran, Prathap Chandran; Patel, Pitambar; Malekar, V. Pushpa; Maya, V. K.; Ramana, V. Chepuri (Journal of Chemical Sciences, 2021)

Ru-catalyzed asymmetric transfer hydrogenation of racemic /3-keto γ-lactams via dynamic kinetic resolution - Malekar, V. Pushpa; More, V. Ganesh; Ramana, V. Chepuri (Tetrahedron, 2024)
The enantioselective transfer hydrogenation of racemic /3-keto gamma-lactams via dynamic kinetic resolution using a chiral Ru(II) catalyst has been developed for the synthesis of optically active /3-hydroxyl lactams with excellent conversion (up to 99 %), high diastereomeric ratio (dr dr 93:07) and enantiomeric selectivity (89 % ee ). The reaction proceeded by using HCO2H/Et3N 2 H/Et 3 N as hydrogen donor and features mild, additive free reaction conditions, fast crystallization, broad substrate scope, and an operationally simpler setup than that for molecular hydrogenation.
Keywords: (R)-1-((R)-Pyrrolidin-3-yl)ethan-1-ol; /3-keto gamma-lactams; Asymmetric transfer hydrogenation; Dynamic kinetic resolution; Fluroquinolone antibiotics